Associations between BMI Change and Cardiometabolic Risk in Retired Football Players. Issue 4 (April 2018) - TREXLER, ERIC T.; SMITH-RYAN, ABBIE E.; DEFREESE, J. D.; MARSHALL, STEPHEN W.; GUSKIEWICZ, KEVIN M.; KERR, ZACHARY Y.
ABSTRACT: Purpose: Elevated rates of cardiometabolic diseases have been observed in former American football players. The current study sought to determine whether change in body mass index (ΔBMI) after retirement influences the prevalence of CHD, diabetes, or high blood pressure (HBP) in former professional football players. Methods: Retired professional football players ( n = 3729) were sent a survey with questions regarding health status, playing history, and demographic information. Self-reported BMI at the time of retirement was subtracted from current self-reported BMI to calculate ΔBMI. Prevalence of CHD, diabetes, and HBP were determined by asking participants if they had ever been diagnosed by a health care professional. Binomial regression with a Poisson residual and robust variance estimation was used to compute crude prevalence ratios (PR) and 95% confidence intervals (CI) for each outcome. Adjusted PR values were calculated by adjusting for BMI at the time of retirement, age, years of football experience, race, exercise habits, alcohol use, steroid history, smoking history, and playing position. Results: Complete data were available for 2062 respondents. Prevalence of CHD increased 25%–31% for each five-point increase in ΔBMI after retirement (crude PR = 1.25, 95% CI = 1.03–1.52, P = 0.026; adjusted PR = 1.31, 95% CI = 1.11–1.55, P = 0.001). Diabetes prevalence increased 69%–88% for each five-point ΔBMI increase (crude = 1.88, 95% CI = 1.45–2.44, P < 0.001; adjusted = 1.69, 95% CI = 1.32–2.15, P < 0.001). A five-point increase in ΔBMI was associated with a 35%–40% increase in HBP prevalence (crude = 1.40, 95% CI = 1.27–1.53, P < 0.001; adjusted = 1.35, 95% CI = 1.24–1.47, P < 0.001). Conclusions: After controlling for relevant covariates, postretirement ΔBMI was positively and independently associated with prevalence of CHD, diabetes, and HBP. Postretirement interventions using diet and/or exercise to influence body composition may improve long-term health in retired football players.